Correlation of gene polymorphisms of CD36 and ApoE with susceptibility of Alzheimer disease: A case–control study. Issue 38 (September 2018) - Zhou, Li; Li, Hai-Yan; Wang, Ji-Hui; Deng, Zhe-Zhi; Shan, Yi-Long; Tan, Sha; Shi, Yi-Hua; Zhang, Ming-Xing; Liu, San-Xin; Zhang, Bing-Jun; Hong, Ming-Fan; Lu, Zheng-Qi; et al.
Abstract : Abstract: This research was aimed to explore correlation of gene polymorphisms of CD36 and ApoE with susceptibility of Alzheimer disease (AD). This study was a case–control study. Two hundred eleven AD hospitalized patients were selected as the AD group and 241 subjects were selected as the control group. PCR-RFLP was used to detect three loci (rs7755, rs3211956, and rs10499859) of CD36 gene and ApoE genotype. Chi-square test and univariate nonconditional logistic regression analysis were used to calculate the odds ratio (OR) and 95% confidence interval (95% CI). The haplotypes were constructed using SHEsis online software and the correlation between haplotypes and AD was analyzed. Meanwhile, differences of 3 alleles of ApoE and 6 genotypes (E2/E2, E2/E3, E2/E4, E3/E3, E3/E4, E4/E4) were compared between AD and control groups. The frequencies of rs7755 genotype (χ 2  = 10.780, P  = .005) and allele (χ 2  = 10.549, P  = .001) were statistically different between 2 groups. The genotype frequency of rs3211956 was statistically different between AD and control groups (χ 2  = 10.119, P  = .006). For the rs7755 locus, GG genotype (OR: 2.013, 95% CI: 1.098–3.699) was an independent risk factor for AD compared with AA genotype. In the dominant model, the risk to develop AD in AG/GG genotype was 1.686 times higher than AA genotype. For the rs3211956 locus, compared with TT genotype, GT genotype (OR: 0.536, 95% CI: 0.340–0.846) was a protective factor for AD after adjusting various physiological and biochemical factors. In the dominant model, the risk of GT/GG genotype to develop AD was reduced by 41.6%. For ApoE gene, the distribution differences of E2/E3 (χ 2  = 9.216, P  = .002), E3/E4 (χ 2  = 7.728, P  = .005), and E4/E4 had statistical significance between the 2 groups. The frequencies of allele E2 (χ 2  = 9.359, P  = .002) and E4 (χ 2  = 13.995, P  < .001) were statistically significant between AD and control groups. The rs7755 and rs3211956 loci polymorphisms of CD36 gene and genotype E2/E3, E3/E4, E4/E4 of ApoE gene, and E2 and E4 alleles were statistically related with AD.